ANALISIS YURIDIS PENGURUSAN HARTA KEKAYAAN ANAK ANGKAT DI BAWAH UMUR PADA WNI KETURUNAN TIONGHOA (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR : 2161 K/PDT/2011) - POSAN POSAN (PREMISE LAW JURNAL, 2015)
Child adoption can be considered as a legal act which assigns a child from his   biological parents to the other parents who will be responsible for his care and education; the adoptive parents have to  bring him up in their own surrounding according to the Ruling of the District Court. The research used judicial normative with descriptive analytic approach. The result of the research showed that the legal guardian, Amini Nurdin, filed a complaint to the defendant I, Lim Agek alias Agek and the defendant II, Lim Asiong alias Asiong. The Supreme Court of the Republic of Indonesia vacated the Rulings of Pakanbaru District Court and of Pakanbaru Appellate Court and stated that the defendant I, Lim Agek alias Agek and the Defendant II, Lim Asiong alias Asiong had performed breach of contract or default and required both of them to return the three ingots of pure gold owned by the three under-aged adopted children to their legitimate guardian, Amini Nurdin, based on the Court’s Ruling. Keywords: Taking Care of Property, Under-Aged Child, Guardianship for the Chinese Ethnic Group